The Impact of Supply Chain Integration on Supply Chain Visibility in Manufacturing Firms in Uganda - Prossy Nuwenyine (Uganda Christian University, 2023)
The study examined the impact of supply chain integration on supply chain visibility in manufacturing firms in Uganda: a case of Century Bottling Company (Coca Cola). It specifically focused on; examining the relationship between supplier integration and supply chain visibility in manufacturing firms, examining the drivers of supply chain integration in manufacturing firms in Uganda and examining the key success factors for supply chain integration in manufacturing firms in Uganda. The study was carried out using a cross sectional survey research design where both quantitative and qualitative research approaches were also used. The data was collected using questionnaires and interviews during the data collection, both purposive and stratified sampling methods were used. A sample size of 80 respondents who are management and employees of Century Bottling Company (Coca Cola) was also used in the study. From the findings, it was revealed that supplier ICT systems are demonstrated to significantly enhance supply chain visibility, offering real-time inventory tracking, proactive disruption management, and improved collaboration with suppliers. The drivers for integration revolve around the complexities of operational processes and competitive pressures, along with motivations for reduced lead times, enhanced product quality, and market advantage. Effective coordination, adaptability, and collaborative partnerships emerge as pivotal success factors for supply chain integration, underscoring the significance of agility and cohesive relationships in optimizing integration efforts. These findings collectively contribute to a deeper understanding of the intricate interplay between technological, operational, and strategic facets in fostering successful supply chain integration within Ugandan manufacturing firms. The study recommended that Century Bottling Company should invest in advanced supplier ICT systems, leverage key integration drivers, foster robust collaboration with partners, empower an adaptable workforce through training, and establish an ongoing process for KPI monitoring. By embracing these strategies, the company can enhance supply chain visibility, streamline operations, and strengthen market competitiveness, ultimately contributing to a more integrated, efficient, and responsive supply chain ecosystem.
This is a dissertation.